The SELFNET Approach for Autonomic Management in an NFV/SDN Networking Paradigm. (14th February 2016) - Neves, Pedro; Calé, Rui; Costa, Mário Rui; Parada, Carlos; Parreira, Bruno; Alcaraz-Calero, Jose; Wang, Qi; Nightingale, James; Chirivella-Perez, Enrique; Jiang, Wei; Schotten, Hans Dieter; Koutsopoulos, Konstantinos; et al.
Abstract : To meet the challenging key performance indicators of the fifth generation (5G) system, the network infrastructure becomes more heterogeneous and complex. This will bring a high pressure on the reduction of OPEX and the improvement of the user experience. Hence, shifting today's manual and semi-automatic network management into an autonomic and intelligent framework will play a vital role in the upcoming 5G system. Based on the cutting-edge technologies, such as Software-Defined Networking and Network Function Virtualization, a novel management framework upon the software-defined and Virtualized Network is proposed by EU H2020 SELFNET project. In the paper, the reference architecture of SELFNET, which is divided into Infrastructure Layer, Virtualized Network Layer, SON Control Layer, SON Autonomic Layer, NFV Orchestration and Management Layer, and Access Layer, will be presented.